Asparagus racemosus competitively inhibits in vitro the acetylcholine and monoamine metabolizing enzymes - Meena J.; Ojha R.; Muruganandam A.V.; Krishnamurthy S. (My University, 2025)
Asparagus racemosus (AR) has earlier been reported to possess antidepressant activity possibly mediated through the monoaminergic system, and nootropic and anti amnestic activities possibly through the cholinergic system. In the present study to further understand the mechanism of action, we evaluated the kinetics of acetyl (AChE) and butyryl (BuChE) cholinesterases, and monoamine oxidase (MAO-A and B) enzyme inhibitory activities of different fractions of AR. The results showed that methanolic extract of AR (MAR) significantly inhibited cholinesterase and MAO activities as compared to hexane (HAR) and chloroform (CAR) extracts of AR as evident from the IC 50 values. The kinetic analysis of enzyme inhibition of MAR shows that the V max does not change with different concentrations of MAR but the K m value increases. This indicates that MAR is a non-selective competitive inhibitor for both cholinesterase and monoamine oxidase enzymes. Evaluation of K i values show that MAR inhibited these enzymes less potently compared to the respective standard drugs. There seems to be a positive correlation between the saponin content and, cholinesterase and monoamine inhibitory activities as MAR had 62.20% of saponins, whereas HAR and CAR had no measurable saponin content. The non-selective competitive inhibitory activity on cholinesterase and monoamine oxidase enzymes can explain many reported neuropharmacological activities of AR. AR apart being used as a drug is also used as a food. As such AR may have potential drug-drug, drug-food and food-food interactions with drugs and foods sharing the cholinergic and monoaminergic pathways. © 2011 Elsevier Ireland Ltd.